Strengthening Digital Literacy through Ethical Education on the Use of Artificial Intelligence and Fact Verification for Students - Rauda Syamsuddin; Nurmiati; Muthofiah; Anisah; Naswa Natania; Ilham Maulana; Andi Wulandari; Ramlah Wulandari (RAM PUBLISHER, 2026)
The rapid development of Artificial Intelligence (AI) has significantly influenced students’ learning activities and access to information. However, the increasing use of AI also raises challenges related to information accuracy, ethical use, and digital responsibility. This community service program aimed to strengthen digital literacy through ethical education on the use of AI and fact verification practices among students at SMK Negeri 5 Palopo. The activity employed a participatory educational approach consisting of presentations, interactive discussions, and practical fact-checking exercises. Students were introduced to digital literacy concepts, ethical AI utilization, information credibility assessment, and misinformation identification. The results showed improved student awareness regarding responsible AI use, fact verification, and academic integrity. Participants demonstrated better understanding of evaluating digital information critically before using or sharing it. The program contributed to strengthening digital literacy competencies and promoting responsible digital citizenship among students.